Investigating the Brand Loyalty of Domestic Cosmetic in an Emerging Market - Mohd Kassim Norizan (EDP Sciences, 2021)
The cosmetic industry in emerging economies such as Malaysia shows vast growth. However, fierce competition has forced domestic cosmetic brands to be more competitive. Brand loyalty is one of the key aspects of management to retain the competitive advantages of the market. Thus, this research would like to investigate the factors that led to the brand loyalty of the domestic cosmetics brand in Malaysia. There are four independent variables in this study, namely brand price, brand perceived value, brand satisfaction, and brand trust, while brand loyalty is a dependent variable. A correlation study was conducted to determine whether there is a positive relationship between the dependent variable and the independent variable. The purpose of this study is twofold: First, to examine the level of loyalty of domestic consumer brands; second, to investigate the relationship between brand prices, brand satisfaction, brand trust, and brand perceive value to the brand loyalty of cosmetic brand. A survey was conducted to measure these variables. A total of 200 useable questionnaires were collected from a commercial hub in Malaysia. Descriptive and correlation analysis were used to investigate the level of loyalty and to test the relationship between these variables.